Construction of an adaptable and specific severity score for prehospital emergencies. Issue 7 (22nd June 2009) - Hubert, H; Guinhouya, C; Wiel, E; Vilhelm, C; Goldstein, P
Abstract : The aim of this study was to design a severity score specific to mobile emergency and resuscitation services (MERS). A prospective, multicentre cohort study including 17 868 patients was performed. The severity reference criterion was determined by multiple correspondence analysis. A multiple linear regression was used for the construction of the severity score. The score performances were analysed in terms of area under the receiver operating characteristics curves (AUC). Twelve variables were identified for the construction of the severity score. The multiple regression (r2 = 0.947; p<0.001) provided a severity score that took on values from 8 to 68. The score performs well in distinguishing the various patient outcomes in terms of AUC. This study develops the first adaptable and specific severity score of MERS activities.